2021
DOI: 10.1017/s095026882100087x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 re-infection in Shahroud, Iran: a follow-up study

Abstract: Although many people became infected and recovered during the Covid-19 epidemic, the immunity duration and reinfection in recovered patients has recently attracted many researchers. The aim of this study was to evaluate the recurrence of the infection in recovered individuals over a 9 month period after onset of the Covid-19 epidemic.In this study, data related to Covid-19 patients in Shahroud city were collected using the electronic system for registering suspicious patients and also by checking patients' hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…[ 8 , 20 , 21 , 23 , 25 , 28 32 , 34 , 36 , 37 ] Six studies reported on 13 hospitalized patients who were reinfected. [ 23 , 25 , 26 , 28 , 35 , 37 ] Among the six studies describing CT values, [ 21 , 23 , 33 , 34 , 36 , 37 ] one had mean CT values of 32.9, [ 33 ] and five had CT values of <30. [ 21 , 23 , 34 , 36 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 , 20 , 21 , 23 , 25 , 28 32 , 34 , 36 , 37 ] Six studies reported on 13 hospitalized patients who were reinfected. [ 23 , 25 , 26 , 28 , 35 , 37 ] Among the six studies describing CT values, [ 21 , 23 , 33 , 34 , 36 , 37 ] one had mean CT values of 32.9, [ 33 ] and five had CT values of <30. [ 21 , 23 , 34 , 36 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the rate and type of immune response, severity and rate of reinfection may vary from society to society [6]. A recently study showed that most people infected with COVID-19 showed antibody response between 10 and 14 days after infection whereas in some mild cases, detection of antibodies requires a long time after symptoms, and in few cases, antibodies are not detected at all.…”
Section: Introductionmentioning
confidence: 99%
“…Viral reinfection is not uncommon, and it occurs with several respiratory viral infections. Moreover, reinfection with respiratory viruses may be explained by an insufficient immune response or infection with another genotype or species of virus as well as the diversity of viral serotyping [ 8 ]. There have been several reports from multiple countries of patients having repeat positive tests for SARS-CoV-2 after recovering from COVID-19 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reinfection with respiratory viruses may be explained by an insufficient immune response or infection with another genotype or species of virus as well as the diversity of viral serotyping [ 8 ]. There have been several reports from multiple countries of patients having repeat positive tests for SARS-CoV-2 after recovering from COVID-19 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. A case report from South Korea identified 163 patients who had repeat positive test results for SARS-CoV-2 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation